(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ramli MP, Malek S, Milow P, Aziz NJ. 2021. Traditional knowledge of medicinal plants in the Kampung Orang Asli Donglai Baru, Hulu Langat, Malaysia. Biodiversitas 22: 1304-1309. Documentation on traditional knowledge of medicinal plants is important before it is completely exhausted by the loss of natural habitats surrounding it and the passing away of older generations. In this study, an ethnobotanical survey for the medicinal plants in the Kampung Orang Asli Donglai Baru, Hulu Langat, Selangor, Malaysia was carried out. A semi-structured interview was prepared to record the medicinal uses of the local medicinal plants in the study area. The information such as the Orang Asli local name, parts used for medication, methods of preparation, and type of ailments were all collected. The total numbers of recorded species in the study sites were 39 species belonging to 22 families. The families Zingiberaceae, Marantaceae, Leguminosae, Vitaceae, Lamiaceae, Melastomataceae, and Araceae have recorded the highest species of medicinal plants. The most frequently utilized plant parts were the leaves (25%) followed by roots (20%), whole plants (10%), fruit (5%) and flowers (2.5%). Gastrointestinal problems including stomach ache, diarrhea, indigestion and bloating were among the most frequent ailments treated with the medical plants. This study revealed that many medicinal plants are still broadly used by the community for treating various diseases in ailments. Further investigation needs to be carried out to explore the potential of these plants in scientific usage.